Being Anxious, Thinking Positively: The Effect of Emotional Context on Respiratory Sensory Gating - Chan, Pei-Ying S.; Cheng, Chia-Hsiung; Jhu, Ya-Jhih; Chen, Chia-Ling; von Leupoldt, Andreas (Frontiers in Physiology, 2016)
Respiratory sensory gating function has been found decreased by induced negative emotion in healthy adults. The increased ratio of the respiratory-related evoked potential (RREP) N1 peak amplitude for the second occlusion (S2) versus the first occlusion (S1), S2/S1, is indicative of such decreased respiratory sensory gating. In this study, we tested the hypothesis that a positive emotional context would enhance respiratory sensory gating function in healthy individuals. In addition, we tested the modulating role of individual anxiety levels. We compared respiratory sensory gating in 40 healthy individuals by the paired inspiratory occlusion paradigm in a positive and neutral emotional context induced by emotional picture viewing. The results showed that the group averaged RREP N1 peak amplitudes S2/S1 ratios were significantly smaller in the positive compared to neutral context (0.49 vs. 0.64; p < .01). Further analysis showed that the ratio decrease was due to a reduced response to the S2 and an enhanced response to S1 in the positive emotional context (p < .05). The subgroup analyses showed that in the positive emotional context, both individuals with low-moderate anxiety levels and those with no anxiety demonstrated a significant decrease of their S2/S1 ratio, but only those with low-moderate anxiety levels showed reduced S2 amplitudes compared to the neutral context (p < .01). In conclusion, our results suggest that a positive emotional context is related to better brain inhibitory mechanisms by filtering out repetitive respiratory stimuli in healthy individuals, especially in the presence of low-moderate anxiety levels. Further investigation on how positive emotional contexts might contribute to improved respiratory sensory gating ability in clinical populations is necessary.